Modeling Malaysia Debt Threshold : Debt Composition Perspective - Venus, Khim-Sen Liew; Jerome, Kueh; Yong, Sze Wei (International Journal of Business and Society (IJBS), 2017)
This study intends to examine the effect of the debt on economic growth of Malaysia from the perspective of domestic debt and external debt. Furthermore, the impact of different type of debts on growth upon either above or below certain threshold level of the debt also investigated using Threshold regression method for sample period 1980-2015. Empirical findings indicate that the threshold level for domestic debt is approximately 37% of GDP while 4% of GDP for external debt. Initial domestic debt accumulation contributes positively to the economic growth of Malaysia when the domestic debt level is below the threshold level but becomes detrimental to economic growth when the debt level exceeds the threshold level. On the other hand, external debt has negative impact on the economic growth when the debt is below the external debt threshold and become positive when exceed the threshold level. In terms of policy recommendation, government has an uphill task in managing the debt at optimal level as different type of debts and levels of debt may have different impact on the economic growth.